Penerapan Six Sigma untuk Pengendalian Kualitas Produksi di Industri Packaging - Faza Ulinnuha; Dika Rahayu Widiana; Wiediartini Wiediartini (Proceedings Conference On Design Manufacture Engineering And Its Application, 2019)
Abstract – A packaging industry in Surabaya is engaged in the production of plastic packaging.Based on 2018 data, there is a product that has the largest percentage of defects, namely PT004cover Eva Mulia (12.7%). Primary ex treatment is the most dominant problem among other disabilitycategories with a percentage of 43%. The purpose of this study is to know and identify the factors thatcause the many defects in the primary ex treatment category and determine alternative improvementpolicies that can reduce the rate of occurrence of primary Ex treatment defects. The Six SigmaDMAIC approach (Define, Measure, Analysis, Improve, Control) is done to overcome this problem.3.35 sigma was obtained from the DPMO calculation in the measure phase and from making a pchart type control chart known that the production process is not statistically controlled. From theanalysis of the causes of the problem using FTA (Fault Tree Analysis), there were 4 factors thatcaused the primary ex treatment defect, the non-sterile environment, there was no standard forprimary administration, the primary material was volatile in the open air, and the primary andprinting processes were carried out separately . As well as handling problems using FMEA (FailureMode and Effect Analysis) and several alternative policy improvements, namely determining the rightdose for the primary and ink mixture, combining the primary giving process and printing process,adding the primer is done together with weighing ink, mixing the primer with ink printing at the sametime in a sterile place, and make a work instruction. The results of the 15-day improvement resultedin a value of 3.8 sigma.